THE KAZAKH LEXICON OF THE VIRTUAL COMMUNICATION - A. Fazylzhanova; A. Serikbaуeva (Scientific Journal of Pedagogy and Economics, 2019)
During the globalization process, various innovations, novelties, new phenomena in every field of society are emerging due to technology and computer equipment. All phenomena occurring in the society are reflected and recorded in the language. The article examines the features of virtual communication compared to real communication, the different features of the language units in virtual communication, the lexicon of social network users which deviate from literary norms of the language and its causes.